Green Synthesis And Characterization of Zinc Oxide Nanoparticles Using Jatropha Curcas for Enhanced Antibacterial Potential - Ovonramwen, Oluwaseyi Bukky; Nwaogu, Ngozi; Okunzuwa, Iyobosa Gift; Omoruyi, Uwaila (Walisongo Journal of Chemistry, 2024)
Green-synthesized nanoparticles offer various advantages over conventionally physico-chemically synthesized nanoparticles. These synthesized nanoparticles have various biological and medicinal applications. In this study, zinc oxide nanoparticles were synthesized using the leaf extract of Jatropha curcas and zinc acetate dihydrate (as a precursor) for nanoparticle synthesis. The optical, functional group, morphological, and structural properties of the synthesized nanoparticles were investigated using ultraviolet-visible spectrophotometers (UV-Vis), Fourier transform infrared (FTIR), and scanning electron microscopy (SEM), and the antibacterial analysis was done using the agar dilution method against some Gram-positive, Staphylococcus aureus, and Gram-negative E. coli, Klebsiella pneumonia, and Pseudomonas aeruginosa. The formation of ZnO NPs was confirmed by a change in the color of the reaction mixture. UV peaks at 290 nm confirm the presence of ZnO NPs. In contrast, the presence of various bioactive functional groups responsible for reducing the bulk zinc acetate dihydrate to ZnO NPs was confirmed using FTIR. SEM analysis showed that the nanoparticles are spherical. Green-synthesized JC-ZnO NPs demonstrated important antibacterial activities when tested against certain bacteria strains; this implies that plant-synthesized nanoparticles can be used to develop many critical biomedical products.